ANALYSIS OF PADDY GROWERS DECISIONS IN LIGHT OF LIMITED IRRIGATION WATER IN THE EUPHRATES BASIN REGION FOR THE PERIOD 1980-2015 - Z. H. Mhmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Paddy is one of the most important nutritional crops. In Iraq, it ranks third after wheat and barley, and first as a summer crop regarding the cultivated area and production. This study aimed to analyze the dynamic nature of supply response of paddy and competitive crops (maize and vegetables) in Euphrates basin to the change in price and to the availability of resources (irrigation water) for the period 1980-2015 using seemingly unrelated regression equation (SUR). To accomplish this aim, main factors affecting paddy supply response were determined. These included paddy price, competitive crops price, production risk, irrigation water and dummy variable to find out the impact of unstable years. Results showed that irrigation water was the most important factor in determining the cultivated areas with these crops. The estimated elasticities suggest that a10% increase in the relative price of paddy, maize, and summer vegetables leads to 3.48%, 5.98% and 0.8% respective increase in cultivated area with these crops in short run and 5.72%, 1.71% and 0.99% respectively in long run. The cross elasticities for these crops were -1.72%, -0.42% and 0.83% respectively in short run and -3.51%, 1.19% and -0.99% respectively in long run which implies the affectivity of irrigation water as a determinant for cultivated area and a restrictor for its response for price change. In the light of these results, it is essential to know the water and land resources before adapting any price policy for rice in order to increase the cultivated area with this crop.